THE EFFECT OF LEARNING MODELS ON MATHEMATICS LEARNING OUTCOMES IN TERMS OF LEARNING INDEPENDENCE IN GRADE VIII - Poni Lestari; Uswatun Khasanah (Universitas Ahmad Dahlan, 2020)
The purpose of this research to whether or not there is a significant effect (1) the Problem Based Learning (PBL) model on the mathematics learning outcomes of VIII grade students of Junior Hih School (SMP) Muhammadiyah 3 Yogyakarta even semester of the 2019/2020 Academic Year (2) the level of learning independence on the learning outcomes of VIII grade students of SMP Muhammadiyah 3 Yogyakarta Even Semester of the 2019/2020 Academic Year, (3) the interaction between the Problem Based Learning model with learning independence on the mathematics learning outcomes of VIII grade students of SMP Muhammadiyah 3 Yogyakarta even semester of the 2019/2020 Academic Year. The population in this research was all VIII grade students of SMP Muhammadiyah 3 Yogyakarta. The random sampling technique took class samples. Data collection techniques used observation and tests. The research instrument was a test of learning outcomes and observation of student independence. The data analysis technique used includes the prerequisite test and hypothesis test. The results of the research at a significant level of 5% with DF= 1 indicate, (1) there is an effect of the Problem Based Learning model in mathematics learning outcomes, obtained Fobs (A) > F0,05; 1; 47, (2) there is an effect of the level of learning independence on mathematics learning outcomes, obtained Fobs (B) > F0,05; 1; 47, (3) there is no significant effect of the interaction between the learning models and learning independence on mathematics learning outcomes, obtained Fobs (AB) < F0,05; 1; 47.